Analysis of the Coal Fluidization Mining Process with the Continuous-Discontinuous Coupled Particle-Block Method. (26th April 2022) - Li, Jing; Feng, Chun; Zhu, Xinguang; Zhang, Yiming
Abstract : In situ fluidization mining is a promising method which shows considerable potential for reducing the ecological influence impacts of coal mining. During fluidization mining, coal gangue will be separated from the ores, filled back, and returned to the excavation region, which, depending on the filling rate, greatly reduces the stratum deformation of strata, depending on the filling rate. Numerical simulations can assist engineers in evaluating stratum deformation and optimizing affordable designs with affordable costs. Accordingly, in this work, a continuous–discontinuous element method is adopted, which is a coupled particle–block finite-discrete element method with an explicit integration formulation, which is adopted for simulating the coal in situ fluidization mining–filling processes. The theory concept of an "equivalent mining height" is utilized to define the backfill mining height. The results partly reveal the influences of the filling rate on the stratum deformation, surface subsidence, and rock burst phenomena, all of which further indicate the advantages of the fluidization mining method.